Simple synthesis of monocyclic pyrimidine-based energetic molecule with “amino–nitro–hydrazino” arrangement - Yuteng Cao; Tianyu Jiang; Ying Li; Honglei Xia; Yu Liu; Wenquan Zhang (FirePhysChem)
With the constant development of energetic materials, numerous explosive molecules have been synthesized, some of which feature competitive performances. However, energetic materials are directly oriented to application requirements. Therefore, more emphasis is gradually placed on route simplification and cost reduction while designing novel energetic molecules. In this work, monocyclic energetic compound 2,4-diamino-6-hydrazineyl-5-nitropyrimidine (3) was successfully obtained. This compound exhibits an alternating “amino–nitro–hydrazino” arrangement, featuring strong intramolecular hydrogen-bonding interaction. With cheap raw material, the whole reaction comprised only two steps, and exhibited simple post processing, only filtration. This novel energetic molecule possesses excellent mechanical security (IS > 40 J, FS > 360 N), acceptable thermal stability (Td = 225 °C), and good detonation parameters (Dv = 8470 m/s, P = 24.9 GPa), indicating that compound 3 may act as a candidate of insensitive explosives.